2015
DOI: 10.1186/s13012-016-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the implementation of interventions to improve the management of chronic kidney disease in primary care: a rapid realist review

Abstract: BackgroundChronic kidney disease (CKD) is common and a significant marker of morbidity and mortality. Its management in primary care is essential for maintenance of cardiovascular health, avoidance of acute kidney injury (AKI) and delay in progression to end-stage renal disease. Although many guidelines and interventions have been established, there is global evidence of an implementation gap, including variable identification rates and low patient communication and awareness. The objective of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 65 publications
3
51
0
1
Order By: Relevance
“…51 Further research into the relationship between trust in the health professional and patient empowerment is warranted. [52][53][54] The implications of these study findings are both theoretical and practical. Given the high levels of professional frustration reported by renal dietitians in this study, it is important to ensure that they have regular professional supervision.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…51 Further research into the relationship between trust in the health professional and patient empowerment is warranted. [52][53][54] The implications of these study findings are both theoretical and practical. Given the high levels of professional frustration reported by renal dietitians in this study, it is important to ensure that they have regular professional supervision.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, findings from a study of patients receiving dietary advice for cardiac rehabilitation indicated that patients stopped following dietary recommendations after receiving contradictory advice from other health professionals . Further research into the relationship between trust in the health professional and patient empowerment is warranted …”
Section: Discussionmentioning
confidence: 99%
“…We included a total of 35 studies in our sample . Most papers reported a single realist review (27 of 35).…”
Section: Resultsmentioning
confidence: 99%
“…A useful summary is given by Taal, which summarizes the evidence for interventions such as eGFR reporting, enhanced prompts with eGFR, the role of pay for performance, audit-based education, and telemedicine 96. Features associated with successful implementation of CKD interventions in primary care include: framing CKD in the context of general well-being and vascular health as well as in terms of patient safety and medicines management; ensuring compatibility with existing clinical practice or with patient’s everyday lives; and enabling ownership of feedback processes to create individualized improvements 97. Other important considerations are clear mechanisms for CKD detection in those at risk as well as appropriate training for health practitioners, particularly in parts of the world where primary care may be less established but where CKD prevalence and impact are increasing 98…”
Section: Managing People With Ckdmentioning
confidence: 99%